Complete mitochondrial genome of Sri Lankan Junglefowl (Gallus lafayetti) and phylogenetic study - Nalini Yasoda Hirimuthugoda; Adeniyi C. Adeola; Xing Chen; Patthamesthrige Wimal Anthony Perera; Weligalle Wedarallage Dewar Asoka Gunawardena; Humpita Gamaralalage Thilini Nisanka Gunwardana; Ting-Ting Yin; Ming-Shan Wang; Gui-Mei Li; Min-Sheng Peng; Ya-Ping Zhang (Mitochondrial DNA. Part B. Resources, 2018)
The complete mitochondrial genomes of two Sri Lankan junglefowl (Gallus lafayetti: CJF) individuals were sequenced by using next-generation sequencing technique. Samples were collected from Rathnapura and Pelmadulla areas in Sri Lanka. The complete mitochondrial DNA is 16,839 bp in length, with a typical mitogenome structure composed of a non-coding control region, 22 tRNA, two rRNA, and 13 protein-coding genes. Overall base composition is 30% A, 23.9% T, 32.3% C, and 13.6% G indicating high content of 54.0% A + T for both individuals. Phylogenetic analysis reveals that CJF samples cluster with the clade of the green junglefowl (Gallus varius) and red junglefowl (Gallus gallus) than to grey junglefowl (Gallus sonerattii: GyJF). This result can be subsequently used to provide essential information for junglefowl evolution.